Handicraft Product Innovation “Mirror Painting” In Cipete Village, Serang City, Banten - Muhammad Nawawi; Gita Sapitri; Grace Victoria (MOVE: Journal of Community Service and Engagement, 2023)
The surplus of human resources in Cipete village is quite potential. This makes it a promising potential to be developed into a labor-intensive village. This community empowerment and training program aims to develop the potential of human resources in Cipete to produce handicraft products that have better value added and can make the community have a prosperous independent economy. After this program is implemented, the results obtained are the development of handicraft products that are unique, interesting, and innovative and have sufficient selling value, and also make the surrounding community better understand the flow of products from upstream to downstream by utilizing the potential that exists around the environment, both human and natural resources.